2018
DOI: 10.1007/s11414-018-9601-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Quality of Care in Community Mental Health: Validation of Concordant Clinician and Client Quality-of-Care Scales

Abstract: Measuring quality of care can transform care, but few tools exist to measure quality from the client's perspective. The aim of this study was to create concordant clinician and client self-report quality-of-care scales in a sample of community mental health clinicians (n = 189) and clients (n = 469). The client scale had three distinct factors (Person-Centered Care, Negative Staff Interactions, and Inattentive Care), while the clinician scale had two: Person-Centered Care and Discordant Care. Both versions dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…Interventions to lessen provider stigma may consider how to address individual-level and organizational-level factors contributing to experiences of discordant care, while amplifying processes contributing to the experience of concordant care. This assertion is consistent with research showing that discordant care and stigma are associated with staff burnout (Charles & Bentley, 2018; Luther et al, 2019). Perceptions of stigma from professionals may reinforce internalized stigma and interfere with successful therapeutic interactions, negatively impacting the quality and effectiveness of mental health treatment (Wang, Link, Corrigan, Davidson, & Flanagan, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interventions to lessen provider stigma may consider how to address individual-level and organizational-level factors contributing to experiences of discordant care, while amplifying processes contributing to the experience of concordant care. This assertion is consistent with research showing that discordant care and stigma are associated with staff burnout (Charles & Bentley, 2018; Luther et al, 2019). Perceptions of stigma from professionals may reinforce internalized stigma and interfere with successful therapeutic interactions, negatively impacting the quality and effectiveness of mental health treatment (Wang, Link, Corrigan, Davidson, & Flanagan, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Quality of care provided to clients was assessed through two scales developed by Luther and colleagues (2019); the scales consisted of a 12-item person-centered, or concordant care, scale (e.g., “I feel I provided high quality services to clients”; α = .77) and a 10-item discordant care scale (e.g., “I took a long time responding to certain clients’ requests”; α = .82). Participants reported how frequently each item occurred in the past 6 months on a 6-point Likert-type scale, with higher scores on each scale reflecting greater concordant or discordant care.…”
Section: Methodsmentioning
confidence: 99%
“…Sustainable change in Youth Care can only be achieved in cooperation with all parties involved, especially parents and their children [1]. Previous studies have shown that client perspectives demonstrate low convergence with quality indicators based on clinicans, research, and policy [2,3]. Clients often value functional outcomes in the context of everyday living and quality of life over control of their illness [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Clients often value functional outcomes in the context of everyday living and quality of life over control of their illness [ 4 5 ]. Moreover, incorporating client perspectives into clinical practice is associated with improved working alliance, increased satisfaction with services and autonomy support [ 3 ]. Thus, to provide integrated Youth Care responsive to the needs of families, it is essential to incorporate parental perspectives into clinical practice [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have developed a self-report quality of care scale, encompassing the IOM’s six domains of quality of care (Luther et al, 2019; Salyers et al, 2015). The revised scale revealed two subdomains of quality of care perceived by those who provide direct services to mental health service consumers (Luther et al, 2019). The two subdomains include person-centered care (capturing the two IOM’s quality of care domains: patient-centered and effective care) and discordant care (capturing the relative absence of four IOM’s quality of care domains: safe, equitable, efficient, and timely care).…”
mentioning
confidence: 99%